Variasi Maksud Kata Emotif “Wela” dalam Bahasa Jawa: Perspektif Sosiopragmatik - Kunjana Rahardi (Badan Pengembangan dan Pembinaan Bahasa, 2020)
This study aims to describe manifestation of the variations of meanings of the emotive word 'wela' in Javanese language. The research data were in the form of snippets of utterances which contain variations of meanings of the Javanese emotive word 'wela'. The source of the substantive data was the daily speech of villagers in which there were manifestations of variations in the meaning of the emotive word 'wela'. The data were collected using the observation and interview method. The observation method was done by using the recording and note-taking technique. The interview method was carried out with the face-to-face interview and the indepth interviewing techniques. The next step is the data identification, data classification, and data typification. Data that had been typified were then subjected to data analysis methods and techniques, but previously triangulated to the experts. Data analysis was performed using extralingual equivalent analysis method. Through this research, six meanings of the emotive word 'wela' have been found in Javanese language, namely: (1) showing the intention of surprise, (2) showing the intention of defense, (3) showing the intention of reminding, (4) showing the intention of surprise, (5) shows the intention of relief to give thanks, (6) shows the intention of disappointment. AbstrakPenelitian ini bertujuan mendeskripsikan variasi manifestasi maksud kata emotif ‘wela’ dalam bahasa Jawa. Data penelitian berupa cuplikan-cupkikan tuturan yang di dalamnya terkandung variasi maksud kata emotif ‘wela’. Sumber data substantifnya adalah tuturan keseharian warga masyarakat perdesaan yang di dalamnya terdapat manifestasi variasi maksud kata emotif ‘wela’. Data dikumpulkan dengan metode simak dan cakap. Metode simak dilakukan dengan teknik rekam dan catat. Metode cakap dilaksanakan dengan teknik cakap semuka dan cakap tansemuka. Langkah selanjutnya adalah identifikasi data, klasifikasi data, dan tipifikasi data. Data yang telah ditipe-tipekan lalu dikenai metode dan teknik analisis data, tetapi sebelumnya ditriangulasikan terlebih dahulu kepada pakar. Analisis data dilakukan dengan metode analisis padan ekstralingual. Melalui penelitian ini telah ditemukan enam maksud kata emotif ‘wela’dalam bahasa Jawa, yakni maksud: (1) menunjukkan maksud keterkejutan, (2) menunjukkan maksud pembelaan, (3) menunjukkan maksud mengingatkan, (4) menunjukkan maksud keheranan, (5) menenunjukkan maksud kelegaan untuk bersyukur, (6) menunjukkan maksud kekecewaan.